"Librería javascript que permita interpretar la escritura de los casos de uso extendidos" - Carvajal Suárez, Dúval Ricardo (2022)
Software modeling helps to visualize the elements necessary to develop a computer system. There are modeling languages that are used to perform this task, however, some developers comment that this phase in software development is very tedious, since the software must be documented and validated before generating the source code. One of the most commonly used diagrams to visualize the computer system is the class diagram. This diagram allows to detail all the classes of objects that will be necessary for the final product to meet the customer’s expectations. Other tools exist to take the system and software requirements, including use cases and user stories. Use cases are used to write down everything that the customer mentions about the operation of the software to be performed through a sequence of actions. The developer should pay attention to everything the customer needs to perform using the system. The use cases are the most convenient to write down the customer’s needs